Impact of Covid-19 on Income of Tilapia (Oreochromis niloticus) and Carp (Cyprinus carpio) Cultivation in Saketi District, Pandeglang Regency, Banten Province - Setiyanto, Ryan Gagas; Mustahal, Mustahal; Putra, Achmad Noerkhaerin (Agrikan Jurnal Agribisnis Perikanan, 2022)
Tilapia is a freshwater fish commodity that is widely cultivated. Another type of fish that is widely cultivated and favored by the community is goldfish. Carp is one type of fish that has high economic value and is widely cultivated because it has a high adaptability to environmental conditions and available food. The fisheries sector has an important role for the country, because it employs many people directly or indirectly, provides food and contributes to survival. The impact of the Covid-19 pandemic is worsening public health, eliminating jobs and people's income. The purpose of this study was to determine the income of tilapia cultivation business actors in Saketi District before and after the covid-19 pandemic and to find out the factors that affect the income of tilapia fish farming business actors in Saketi District after covid-19. The location of data collection is carried out in November-December 2021. Data collection is carried out in Saketi District, Pandeglang Regency, Banten. The location chosen in this research is Saketi District, Pandeglang Regency, Banten. The main impact experienced by cultivators is a declining level of sales and high production costs. The percentage increase in the selling price of tilapia reached 28.57% and the increase in carp reached 62.16% since the start of the pandemic. The dependence of aquaculture business actors on feed results in high production costs, so that aquaculture business actors reduce production in order to overcome the declining amount of income and increasing feed prices.